The third digital divide and Bourdieu: Bidirectional conversion of economic, cultural, and social capital to (and from) digital capital among young people in Madrid - Calderón Gómez, Daniel (New Media & Society, 2021)
Based on Bourdieu's theory, this paper focuses on the third-level digital divide in relation to offline outcomes of Internet use. Based on 30 in-depth qualitative interviews with young people in Madrid, we analyzed the mechanisms used to convert three main forms of capital-economic, cultural and social-into digital capital (DC) and the subsequent reconversion of DC back into the three main forms of capital. We conclude that economic capital is the most basic form of digital inequality, imposing material barriers to access. Cultural capital is transformed into DC through people's techno-socialization, while social capital is converted into DC by means of social practices and social support. DC can be retransformed into each of the three main forms of capital: to economic capital by means of professional networking and access to goods; to cultural capital through access to knowledge; and into social capital by the differential management of social ties.